Shear Strength of Single Lap Joint Aluminium-Thermoplastic Natural Rubber (Al-TPNR) Laminated Composite - M. Z., Muzzakar; S., Ahmad; M. A., Yarmo; A., Jalar; Mohd Bijarimi, Mat Piah (IOP Publishing, 2013)
In this work, we studied the effect of surface treatment on the aluminium surface and a coupling agent to improve adhesion between aluminium with organic polymer. Thermoplastic natural rubber (TPNR) matrix was prepared by melt blending of natural rubber (NR), liquid natural rubber (LNR) compatibilizer, linear low density polyethylene (LLDPE) and polyethylene grafted maleic anhydride (PE-g-MAH). The PEgMAH concentration used was varied from 0% - 25%. In addition, the aluminium surface was pre-treated with 3-glycidoxy propyl trimethoxy silane (3-GPS) to enhance the mechanical properties of laminated composite. It was found that the shear strength of single lap joint Al-TPNR laminated composite showing an increasing trend as a function of PE-g-MAH contents for the 3-GPS surface treated aluminium. Moreover, the scanning electron microscope (SEM) revealed that the strength improvement was associated with the chemical state of the compound involved.